Pengembangan Modul Pembelajaran IPA pada Topik Magnet, Listrik dan Teknologi untuk Kehidupan Berbasis Sains Teknologi dan Masyarakat (STM) Kelas V SDN 22 Lubuklinggau - Widaswari, Dea; Sari Erander (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a science learning module based on Science, Technology, and Society (STS) that is valid, practical, and effective for use in the learning process. The method used is the 4D development model (Define, Design, Develop, Disseminate) and was conducted on fifth-grade students at SDN 22 Lubuklinggau. The developed module was validated by three experts: a language expert, a media expert, and a subject matter expert. The results showed that the language validation received a score of 93 (high category), media validation scored 90 (high category), and material validation also scored 90 (high category). The practicality test, based on teacher and student questionnaire results, showed a percentage of 91%, indicating a very practical criterion. The potential effect test, based on pre-test and post-test scores, showed a gain score of 0.75, which falls into the high classification. In conclusion, the science learning module based on STS developed in this study is proven to be valid, practical, and effective for use in classroom learning. Keywords: Learning Module, Science, STS, Technology